2015
DOI: 10.1016/j.jep.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

An ex vivo approach to botanical–drug interactions: A proof of concept study

Abstract: Ethnopharmacological relevance Botanical medicines are frequently used in combination with therapeutic drugs, imposing a risk for harmful botanical-drug interactions (BDIs). Among the existing BDI evaluation methods, clinical studies are the most desirable, but due to their expense and protracted time-line for completion, conventional in vitro methodologies remain the most frequently used BDI assessment tools. However, many predictions generated from in vitro studies are inconsistent with clinical findings. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Recently, two novel tactics have demonstrated that in vitro methods can be useful predictors of in vivo HDI. An ex vivo approach devised by Markowitz et al and Wang et al revealed that circulating plasma concentrations of goldenseal isoquinoline alkaloids and their metabolites could inhibit CYP isoforms to a degree similar to that observed in a clinical HDI study, lending credence to the physiological relevance of this procedure. This method has the advantage of exposing hepatocytes, isolated CYPs, or other in vitro enzyme/transporter systems to phytochemical species generated during gastrointestinal absorption that are physiologically germane (i.e., parent compounds and metabolites), an aspect frequently neglected in conventional in vitro HDI studies.…”
Section: Herb‐drug Interactions: a Question Of Clinical Relevancementioning
confidence: 73%
“…Recently, two novel tactics have demonstrated that in vitro methods can be useful predictors of in vivo HDI. An ex vivo approach devised by Markowitz et al and Wang et al revealed that circulating plasma concentrations of goldenseal isoquinoline alkaloids and their metabolites could inhibit CYP isoforms to a degree similar to that observed in a clinical HDI study, lending credence to the physiological relevance of this procedure. This method has the advantage of exposing hepatocytes, isolated CYPs, or other in vitro enzyme/transporter systems to phytochemical species generated during gastrointestinal absorption that are physiologically germane (i.e., parent compounds and metabolites), an aspect frequently neglected in conventional in vitro HDI studies.…”
Section: Herb‐drug Interactions: a Question Of Clinical Relevancementioning
confidence: 73%
“…More recently, Wang and colleagues [ 126 ], using an ex vivo approach by plasma/serum samples collected from healthy subjects administered with goldenseal extracts, have confirmed the inhibitory effects towards CYP3A-catalyzed midazolam 1′-hydroxylation. Particularly, the authors have calculated an IC 50 value of 33.03 μM for hydrastine and 473.0 μM for berberine, indicating that hydrastine is more potent in terms of inhibiting CYP3A [ 126 ]. Moreover, concurrent, albeit moderate, inhibition of P-gp in humans [ 127 ] might contribute increasing drug exposure in subjects assuming also goldenseal.…”
Section: Resultsmentioning
confidence: 99%
“…A plethora of articles tested the in vitro interaction of silymarin, or its constituents, mainly racemic silybin, with cytochrome P450 isoforms, 142,168,188–208 UDP‐glucuronosyl transferases, 199,200,202,209 and/or transporters 179,192,198,205,207,210–221 . The data from these articles are summarized graphically in Figures 5 and 6.…”
Section: Interactionsmentioning
confidence: 99%
“…I, intestine; L, liver; M, mouse; P, poor metabolizer or the level of the enzyme was low; R, recombinant enzyme; rP, recombinant enzyme with lower (“poor”) metabolic activity. Source : Data are from References [142,168,188–191,196,198,199,201,202,204–209,211]…”
Section: Interactionsmentioning
confidence: 99%